2021
DOI: 10.3389/fneur.2021.696950
|View full text |Cite
|
Sign up to set email alerts
|

Habituation After Deep Brain Stimulation in Tremor Syndromes: Prevalence, Risk Factors and Long-Term Outcomes

Abstract: Deep brain stimulation (DBS) of the thalamus is an effective treatment for medically refractory essential, dystonic and Parkinson's tremor. It may also provide benefit in less common tremor syndromes including, post-traumatic, cerebellar, Holmes, neuropathic and orthostatic tremor. The long-term benefit of DBS in essential and dystonic tremor (ET/DT) often wanes over time, a phenomena referred to as stimulation “tolerance” or “habituation”. While habituation is generally accepted to exist, it remains controver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 99 publications
(200 reference statements)
0
21
0
Order By: Relevance
“…There is an ongoing scientific debate on the mechanisms involved in delayed therapy escape after Vim DBS mostly focusing on disease progression versus habituation ( Fasano and Helmich, 2019 , Favilla et al, 2012 , Peters and Tisch, 2021 ). We here add a further possibility, namely a direct effect of long term DBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing scientific debate on the mechanisms involved in delayed therapy escape after Vim DBS mostly focusing on disease progression versus habituation ( Fasano and Helmich, 2019 , Favilla et al, 2012 , Peters and Tisch, 2021 ). We here add a further possibility, namely a direct effect of long term DBS.…”
Section: Discussionmentioning
confidence: 99%
“…In general, comparability of studies is limited due to their focus on selected aspects of the phenomenon, which moreover lacks a consensus definition ( Fasano and Helmich, 2019 ; cf. Patel et al, 2014 , Peters and Tisch, 2021 ). Fasano and Helmich (2019) defined this phenomenon as “therapy escape” and coined a consistent nomenclature of associated processes.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason worth considering is habituation. The term “habituation,” previously known as “tolerance,” is referred to as the vanishing of DBS efficacy despite reprogramming that could not be explained by loss of micro-lesional implant effect or disease progression ( Fasano and Helmich, 2019 ; Peters and Tisch, 2021 ). It is mostly reported in cases of essential tremor cases, but the phenomenon has also been described in dystonia patients receiving GPi DBS ( Shah and Jimenez Shahed, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GPi-DBS could normalize excessive cortical plasticity and is one of the fundamental factors for its effect ( Tisch et al, 2007 ; Ruge et al, 2011a ; Barow et al, 2014 ). However, it has been suggested that habituation may also be generated from neural reorganization ( Dostrovsky and Lozano, 2002 ; Ruge et al, 2011a; Peters and Tisch , 2021 ). And theoretically, it should be noted that STN DBS may also induce habituation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation